2018
DOI: 10.1007/s12649-018-0486-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Sewage Sludge Bioconversion to Methane by the Addition of Exhausted Coffee Biowaste Liquid Fraction

Abstract: Anaerobic co-digestion of organic rich wastes and wastewater sludge has become an attractive economic possibility for water utilities as it enhances biogas production. The suitability of the organic rich waste depends on its biodegradability as well as on its synergetic effect on the anaerobic digestion process. The feasibility of sewage sludge (SS) treatment via co-digestion was studied in a semi-continuous mode at mesophilic conditions (36 ± 1 °C), with a hydraulic retention time of 17 days and an average or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The balance of the C/N ratio of the feedstock was shown to enhance the methane production of anaerobic co-digestion (Mozhiarasi et al, 2019) (Zealand et al, 2018) (Ngan et al, 2019). The proportion between carbon and nitrogen improves the buffering capacity and minimizes the effect of inhibitory compounds (accumulation of organic acids, ammonia, VFAs) (Elalami et al, 2019) (Fragoso et al, 2020) (Shen et al, 2019) (Sahoo & Rao, 2019).…”
Section: Carbon-to-nitrogen (C/n) Ratiomentioning
confidence: 99%
See 3 more Smart Citations
“…The balance of the C/N ratio of the feedstock was shown to enhance the methane production of anaerobic co-digestion (Mozhiarasi et al, 2019) (Zealand et al, 2018) (Ngan et al, 2019). The proportion between carbon and nitrogen improves the buffering capacity and minimizes the effect of inhibitory compounds (accumulation of organic acids, ammonia, VFAs) (Elalami et al, 2019) (Fragoso et al, 2020) (Shen et al, 2019) (Sahoo & Rao, 2019).…”
Section: Carbon-to-nitrogen (C/n) Ratiomentioning
confidence: 99%
“…And less famous, the Chen and Hashimoto model (Sukhesh & Rao, 2018) and the cone model (Achinas & Euverink, 2019) are also used for the kinetic analysis of the AD. Apart from the kinetics model, other methods including specific energy-loading rate where the reactor is stable below 0.4 day −1 (Fragoso et al, 2020), thermal analysis, and the differential scanning calorimetry are also used to assess the AD stability (González et al, 2019).…”
Section: Assessment Of Biodegradability and Synergistic Effect Of The...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies showed that the use of SCG as raw feedstock for biogas production emerges with interesting potential (Girotto et al, 2018; Orfanoudaki et al, 2019). Several studies have reported the anaerobic mono-digestion of SCG (Battista et al, 2016; Girotto et al, 2018; Valero et al, 2016) and co-digestion of SCG with other feedstocks, such as sewage sludge (Fragoso et al, 2018; Neves et al, 2006), cow manure (Codignole Luz et al, 2018), pig manure (Orfanoudaki et al, 2019) and others (Kim et al, 2017). In general, it was highlighted that SCG have high potential for biogas production; on the other hand, it can lead to high production of volatile fatty acids (VFAs) with a fast reduction of the slurry pH and, thus, cause a possible perturbation of the AD process (Codignole Luz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%